2018
DOI: 10.2196/jmir.9547
|View full text |Cite
|
Sign up to set email alerts
|

Effect and Process Evaluation of e-Powered Parents, a Web-Based Support Program for Parents of Children With a Chronic Kidney Disease: Feasibility Randomized Controlled Trial

Abstract: BackgroundParents of children with chronic kidney disease (CKD) experience high levels of stress in the daily management of their child’s illness. Parents need continuously available support and information, yet online support programs are lacking. e-Powered Parents was developed to fill this gap; it is an online program consisting of (1) medical information, (2) an interactive part, and (3) four training modules (stress management, setting limits, communication, and coping). Prior to a large-scale evaluation,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 37 publications
0
11
0
1
Order By: Relevance
“…Similar results have been seen in online psychoeducation interventions for alcohol misuse, anxiety, depression, and smoking cessation—usage analytics over a period of more than 10 years demonstrated that 90% of peer group participants lurked, rather than contributing to discussions (van Mierlo, ). Minimal participation in online psychoeducation programmes using voluntary, self‐directed peer discussion forums was also demonstrated by Cristancho‐Lacroix et al () in an investigation of Alzheimer's caregivers, by Geense et al () in an investigation of caregivers of children with chronic kidney disease, and by Steed () in an investigation of parenting attachment issues.…”
Section: Introductionmentioning
confidence: 77%
“…Similar results have been seen in online psychoeducation interventions for alcohol misuse, anxiety, depression, and smoking cessation—usage analytics over a period of more than 10 years demonstrated that 90% of peer group participants lurked, rather than contributing to discussions (van Mierlo, ). Minimal participation in online psychoeducation programmes using voluntary, self‐directed peer discussion forums was also demonstrated by Cristancho‐Lacroix et al () in an investigation of Alzheimer's caregivers, by Geense et al () in an investigation of caregivers of children with chronic kidney disease, and by Steed () in an investigation of parenting attachment issues.…”
Section: Introductionmentioning
confidence: 77%
“…Table 2 provides a summary of respondent demographics according to telehealth survey instrument use. Telehealth survey instruments have primarily been used to assess patient experience (n=41, 91%) 23 , 24 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 with less frequent use to assess family caregiver (n=7, 16%) 28 , 34 , 37 , 40 , 65 , 66 or medical provider experience (n=8, 18%). 23 , 35 , 40 , 67 , 68 , 69 , 70 , 71 …”
Section: Resultsmentioning
confidence: 99%
“…Table 2 provides a summary of respondent demographics according to telehealth survey instrument use. Telehealth survey instruments have primarily been used to assess patient J o u r n a l P r e -p r o o f experience (n=41, 91%) 23,24, with less frequent use to assess family caregiver (n=7, 16%) 28, 34,37,40,65,66 or medical provider experience (n=8, 18%). 23,35,40,[67][68][69][70][71] Telehealth surveys have been under-utilized to assess the experience of pediatric or adolescent cohorts with only two (4%) surveys used to assess the experience of pediatric care experiences or pediatric family caregiver experiences: TeSS for use in pediatric surgery telehealth communication 72 and TAM for pediatric telehospice care.…”
Section: Previous Populationsmentioning
confidence: 99%
“…Data were analyzed using MAXQDA10 software. A conventional six-step content analysis [24] was used to analyze data and including 1. reaching a general understanding by immersion and reading the transcription several times to detect primary ideas, 2. creating primary codes in the transcription by re-reading line by line, 3. searching for and determining categories and sub-categories, 4.…”
Section: Discussionmentioning
confidence: 99%